Aplikasi Building Information Modeling (BIM) Menggunakan Software Tekla Structures 2022 Pada Konstruksi Gedung Asrama Putra Ponpes Amanatul Ummah, Kabupaten Mojokerto, Jawa Timur - Damasus Budi Harjon; Nawir Rasidi; Handika Setya Wijaya; Diana Ningrum (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
The development of Building Information Modeling (BIM) technology has greatly contributed to improving the efficiency of the construction planning and implementation process. This study discusses the application of BIM in the construction project of the Putra Pondok Pesantrean Amanatul Ummah dormitory building in Mojokerto, East Java, using Tekla Structures. The main objectives of this study are to produce a three-dimensional (3D) structural model, create a four-dimensional (4D) implementation schedule, and compile a five-dimensional (5D) cost estimate. This research uses a case study method by processing project shop drawing data, which is then modeled using Tekla Structures. The structural modeling process begins with the foundation, sloof, columns, beams, and floor slabs. The resulting 3D model is then combined with the construction schedule to form a 4D simulation and calculate the cost estimate through 5D modeling. The results of the study show that the modeling of the Foundation, Sloof, Columns, Beams & Floor Slabs (3D) structures has been carried out. From the 4D simulation, the project implementation schedule starts on January 2, 2025, and ends on November 11, 2025. The total calculation of the Cost Estimate (RAB) for the structural work is IDR 3,043,967,282 (three billion forty-three million nine hundred sixty-seven thousand two hundred eighty-two rupiah).